Warming drives phenological changes in coastal zooplankton - Forsblom, Louise; Stoffers, Tjardo; Lindén, Andreas; Lehtiniemi, Maiju; Engström-Öst, Jonna (Springer Nature, 2024)
Climate warming has led to phenological changes over time, typically displayed as earlier emergence of various organisms in spring or summer in temperate terrestrial and marine systems alike. Similarly, warm conditions can extend seasonal occurrence. Using a time series of zooplankton data from a coastal area in the Gulf of Finland, we calculated the start, end and the length of the season for the occurrence in rotifers and for adult and juvenile stages of three calanoid copepods. We investigated whether the start and end of the season of these taxa have shifted earlier and later, respectively, and whether the season length has increased. We further investigated if potential changes are driven by climate warming. We show that both copepods and rotifers do indeed emerge earlier, but that the pattern in recent years was not conclusive, and that both temperature and ice conditions influenced the seasonal abundance patterns of some taxa. Warmer years led to earlier occurrence of Temora longicornis copepodites. Earlier ice break-up coincided with longer seasons for Acartia and earlier emergence of Eurytemora affinis. The phenological changes in zooplankton demonstrated here may have cascading effects on other trophic levels in the food web. We also demonstrate how decreased sample number influences the ability to capture intra-annual abundance patterns and discuss the implications for monitoring.
Keywords: Phenology; Climate change; Zooplankton; Monitoring